2013
DOI: 10.1007/s10750-013-1648-9
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced genetic differentiation of small, isolated and fragmented tilapia populations inhabiting the Magadi Soda Lake in Kenya

Abstract: Lake Magadi, an alkaline hypersaline lake in Kenya, is one of the most extreme water bodies known. Although its water temperatures often exceed 40°C, a particular lineage of 'dwarf' tilapia, Alcolapia grahami, has evolved remarkable adaptations to survive in this hostile environment. Magadi tilapia exists in small fragmented populations in isolated lagoons within Lake Magadi and its satellite Lake, Little Magadi. In spite of the potential this tilapia holds for understanding evolutionary processes in stressful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 52 publications
3
29
0
Order By: Relevance
“…This is corroborated by a recent study based on microsatellite markers that revealed three genetically distinct population clusters of Magadi tilapia designated as FSL, ROM and LM (Kavembe et al . ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This is corroborated by a recent study based on microsatellite markers that revealed three genetically distinct population clusters of Magadi tilapia designated as FSL, ROM and LM (Kavembe et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…, ; Kavembe et al . ). However, a recent study found significant genetic exchange between populations of congeneric species inhabiting various lagoons of Lake Natron (Zaccara et al .…”
Section: Introductionmentioning
confidence: 97%
“…The metabolic differences observed could be phenotypic, genotypic or both. At present, it is unclear whether the FSL and SWHS populations are genetically distinct567. With respect to the current debate about the O 2 -and capacity-limited thermal tolerance (OCLTT) hypothesis2425, the pattern of aerobic metabolism in FSL fish (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High pH often negatively affects nitrogen waste excretion, whereas intense ultraviolet radiation and ROS have detrimental effects on several cellular components including lipid peroxidation, protein carbonylation, and degradation of genetic material (DNA and RNA) (Rothschild and Mancinelli 2001). Surprisingly, despite these stressful conditions, A. grahami maintains viable populations in Lake Magadi, which do not show signs of reduced genetic diversity (Seegers et al 1999;Wilson et al 2000Wilson et al , 2004Kavembe et al 2014).…”
mentioning
confidence: 99%
“…Geological studies suggest the extreme conditions in Lake Magadi were initiated by a Pleistocene desiccation event (about 13,000 years ago) that resulted in the splitting of a freshwater paleolake Orolonga to form the present-day Lake Magadi, Lake Little Magadi (a small soda lake located North of Magadi), and Lake Natron (a large soda lake located South of Magadi). In a recent study (Kavembe et al 2014), we inferred the closest extant relative of both A. grahami and its sister species from lake Natron to be Oreochromis variabilis, a freshwater species endemic to Lake Victoria. It has been suggested that Lake Victoria experienced a Pleistocene desiccation, which might imply a recent origin of its native cichlid species flock, composed of mainly haplochromine cichlids (Seehausen 2002).…”
mentioning
confidence: 99%